One amino acid in mouse activated factor VII defines its endothelial protein C receptor (EPCR) binding and modulates its EPCR‐dependent hemostatic activity in vivo. (14th February 2017) - Pavani, G.; Zintner, S. M.; Ivanciu, L.; Small, J. C.; Stafford, K. A.; Szeto, J. H.; Margaritis, P.
Abstract : Essentials The lack of factor (F) VIIa‐endothelial protein C receptor (EPCR) binding in mice is unresolved. A single substitution of Leu4 to Phe in mouse FVIIa (mFVIIa) enables its interaction with EPCR. mFVIIa with a Phe4 shows EPCR binding‐dependent enhanced hemostatic function in vivo vs. mFVIIa. Defining the FVIIa‐EPCR interaction in mice allows for further investigating its biology in vivo . Summary: Background: Human activated factor VII (hFVIIa), which is used in hemophilia treatment, binds to the endothelial protein C (PC) receptor (EPCR) with unclear hemostatic consequences. Interestingly, mice lack the activated FVII (FVIIa)–EPCR interaction. Therefore, to investigate the hemostatic consequences of this interaction in hemophilia, we previously engineered a mouse FVIIa (mFVIIa) molecule that bound mouse EPCR (mEPCR) by using three substitutions from mouse PC (mPC), i.e. Leu4→Phe, Leu8→Met, and Trp9→Arg. The resulting molecule, mFVIIa‐FMR, modeled the EPCR‐binding properties of hFVIIa and showed enhanced hemostatic capacity in hemophilic mice versus mFVIIa. These data implied a role of EPCR in the action of hFVIIa in hemophilia treatment. However, the substitutions in mFVIIa‐FMR only broadly defined the sequence determinants for its mEPCR interaction and enhanced function in vivo . Objectives: To determine the individual contributions of mPC Phe4, Met8 and Arg9 to the in vitro / in vivo properties of mFVIIa‐FMR. Methods: The mEPCR‐binding properties of single amino acid variants of mFVIIa or mPC at position 4, 8 or 9 were investigated. Results and conclusions: Phe4 in mFVIIa or mPC was solely critical for interaction with mEPCR. In hemophilic mice, administration of mFVIIa harboring a Phe4 resulted in a 1.9–2.5‐fold increased hemostatic capacity versus mFVIIa that was EPCR binding‐dependent. This recapitulated previous observations made with triple‐mutant mFVIIa‐FMR. As Leu8 is crucial for hFVIIa–EPCR binding, we describe the sequence divergence of this interaction in mice, now allowing its further characterization in vivo . We also illustrate that modulation of the EPCR–FVIIa interaction may lead to improved FVIIa therapeutics.